2022
DOI: 10.3390/ijerph191811217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low Back Pain and Associated Risk Factors among Saudi Arabian Adolescents: A Cross-Sectional Study

Abstract: Low back pain is the most prevalent musculoskeletal condition. Studies on adolescent low back pain are scarce, with no research to determine its prevalence in Saudi Arabia. This study aimed to assess the prevalence and associated risk factors of low back pain in Saudi Arabian adolescents. This cross-sectional study was conducted among Saudi Arabian high school students, which included demographic data, medical and low back pain history. The completed survey by 2000 participants showcased 57.9% of students expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…[13] A recent study conducted on Saudi Arabian teens revealed that 57.8% of the participants had suffered LBP over 12 months. [14] For young adults, physical exercise and LBP have both direct and indirect impacts. [14] One of the most crucial aspects of health for individuals with LBP is physical activity, which may have an impact on how active they are on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[13] A recent study conducted on Saudi Arabian teens revealed that 57.8% of the participants had suffered LBP over 12 months. [14] For young adults, physical exercise and LBP have both direct and indirect impacts. [14] One of the most crucial aspects of health for individuals with LBP is physical activity, which may have an impact on how active they are on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
“…[14] For young adults, physical exercise and LBP have both direct and indirect impacts. [14] One of the most crucial aspects of health for individuals with LBP is physical activity, which may have an impact on how active they are on a daily basis. [14] Adolescents are more likely than adults to participate in inappropriate behaviors that are detrimental to their health like sedentary lifestyles, physical inactivity, and psychosocial stress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low back pain (LBP), defined as pain and discomfort situated below the costal margin and above the inferior gluteal folds, with or without accompanying leg pain, is among the most common medical conditions (1) . Leading the cause of musculoskeletal disability worldwide, LBP's cost to healthcare systems escalates, creating a significant burden in developed nations as well as low and middle-income countries (2,3) .The high cost of coping with LBP extends beyond financial strain and into a complex interplay of physical, psychological, and social influences affecting a broad demographic of adults, both young and old. Therefore, LBP represents a significant global challenge globally (3 & 4) .…”
Section: Introductionmentioning
confidence: 99%